The genus Sibbaldianthe (Rosaceae): a nomenclatural overview and new combinations - Mosyakin, Sergei L.; Shiyan, Natalia M. (Phytotaxa, 2017)
A nomenclatural overview of the genus Sibbaldianthe (Rosaceae, tribe Potentilleae) is provided, following the recent re-circumscription of genera in subtribe Fragariinae based on molecular phylogenetic and morphological evidence. It is demonstrated that the names Potentilla orientalis and P. semiglabra were in fact published by Yuzepchuk (Juzepczuk) without Latin descriptions in 1935, not in 1934; thus, these names and the combinations based on them are invalid. New combinations are validated: Sibbaldianthe subg. Schistophyllidium (Potentilla subg. Schistophyllidium); Sibbaldianthe imbricata (Potentilla imbricata), S. moorcroftii (P. moorcroftii), S. orientalis (Schistophyllidium bifurcum subsp. orientale, P. orientalis, nom. inval.), and S. semiglabra (Schistophyllidium bifurcum subsp. semiglabrum, P. semiglabra, nom. inval.). Nomenclature, distribution patterns, and data on chromosome numbers of all recognized taxa are discussed. Lectotypes of four names are designated; data on types of other names are provided when available. As currently outlined, the genus Sibbaldianthe contains seven species: two (S. adpressa and S. sericea) in subg. Sibbaldianthe and five in subg. Schistophyllidium.